Mass balance of the Sary-Tor Glacier reproduced from meteorological data - V. V. Popovnin; A. S. Gubanov; R. A. Satylkanov; B. O. Ermenbayev (Лëд и снег, 2021)
Mass balance bn is the most important indicator of a glacier evolution. However, after the decay of the USSR direct measurements of bn performed in 1985–1989 in the Inner Tien Shan, including the Sary-Tor Glacier in Ak-Shiyrak Massif, had been desisted. As a result the available series of the data were limited 1989. Measurements in this area were renewed only in 2015. This paper is devoted to restoring the continuity of the mass-balance series over the period of the gap in measurements and extending this series down to 1929, i.e. to the beginning of regular meteorological observations on the reference HMS Tien Shan (3660 m a.m.s.l.). Accumulation was reconstructed using a linear relationship of bn with the air temperature and precipitation sum. Reconstruction of ablation was based on its cubic relationship with the temperature (modified Krenke– Khodakov formula) or on two-parameter linear approximation using the air temperature and wind velocity. Thereby, the decade of direct instrumental measurements (1984/85–1988/89 and 2014/15–2018/19) resulted in deriving and analyzing continuous 90-year-long series of annual values of bn and its constituents, analytical type of referent glacio-meteorological equations being assumed unchanged in time. Reconstruction for the Sary-Tor Glacier reveals a dominant trend towards the mass loss with rare and short-time episodes of retarding the negative tendencies. The comparison made with the long series of mass balance of other glaciers in Asia indicates a certain degree of synchronicity, which is slightly disturbed in recent years: the degradation of Sary Tor Glacier tends to progress more intensively. Conclusions about its evolution are particularly relevant in connection with the assumption about the impact of the Kyrgyz-Canadian gold mining company «Kumtor Gold Company» on local ecosystems against the background of its interest in expanding the mining zone to the bowels of the Earth under the tongue of this glaciological object.